PRODUÇÃO DE ETANOL DE SEGUNDA GERAÇÃO A PARTIR DE SORO DE LEITE E ÁGUA DE MACERAÇÃO DE MILHO - Farias, Fabiane Oliveira (2015)
The agro-business growth beyond creating positive impacts generates the concern with the high level of by-products generation that require proper disposal. Cheese whey and corn steep liquor are among these by-products with high pollution potential if are simply discarded, but if considered the nutrients present in both of them, they are potential raw materials for obtaining new products. One possible use of those by-products is as substrates for bioethanol production, decreasing the impacts in high waste generation as well as the use of fossil fuels. The aim of this work was to produce bioethanol using the by-products whey and corn steep liquor. Experimental design tools were used to examine their technical viability for secondgeneration ethanol production. The worts, containing 100% corn steep liquor and 25% whey with 75% corn steep liquor, supplemented with glucose were considered superior for bioethanol production with fermentation efficiency reaching around 90 % for both of them. The worts also showed satisfactory results when supplemented with sugar cane molasses or brown sugar. One of the main problems found in ethanol fermentation was the lactic acid generation resulting from contamination with lactic acid bacteria, and in order to overcome that difficulty, pasteurization and use of antibiotics were made and showed good results in controlling contaminants. The use of antibiotics, especially of sodium monensin showed advantages by reducing the maximum rate of growth of yeast (μmax), and as reported elsewhere lower μmax values reflects in higher rates of fermentation efficiency. In general the results were considered satisfactory reaching high level of ethanol productivity (above 1 g L-1 h-1) and maximum fermentation efficiency (Nb) of 93.85 % for the experiment with 100 % of corn steep liquor using monensin sodium antibiotic how to contaminants control.